Youth, Emerging Adults, Faith, and Giving - Patricia Snell Herzog (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This is a book about young people-youth and emerging adults. The contributors investigate the religious and spiritual lives of young people, especially as they relate to inclinations to do good for others. This edited volume is the result of a special issue that invited social scientific insights on responses to these questions. The background for this volume, summarized below, is the evolving life course developmental processes, as well as the culmination of numerous social and cultural changes in recent decades and their implications for socialization of religiosity, spirituality, and generosity. The included chapters focus on the faith and giving of youth and emerging adults, in the United States and internationally. The emphasis is on research that contributes breadth to social scientific understandings of religion, charitable giving, volunteering, generosity, youth, and emerging adults. We are especially interested in trends related to participation in religious and civic organizations, including changing cultural structures, beliefs, and orientations to faith and giving in less formal or non-organizational contexts.